Notch signaling regulates PD‐1 expression during CD8+ T‐cell activation. Issue 1 (16th October 2012) - Mathieu, Mélissa; Cotta‐Grand, Natacha; Daudelin, Jean‐François; Thébault, Paméla; Labrecque, Nathalie
Abstract : Programmed cell death 1 (PD‐1) is an inhibitory receptor involved in T‐cell activation, tolerance and exhaustion. Little is known on how the expression of PD‐1 is controlled during T‐cell activation. Recent studies demonstrated that NFATc1 and IRF9 regulate Pdcd1 (PD‐1) transcription and that T‐bet acts as a transcriptional repressor. In this study, we have investigated the role of the Notch signaling pathway in PD‐1 regulation. Using specific inhibitors of the Notch signaling pathway, we showed decreased PD‐1 expression and inhibition of Pdcd1 transcription by activated CD8 + T cells. Chromatin immunoprecipitation further showed occupancy of the Pdcd1 promoter with RBPJk and Notch1 intracellular domain at RBPJk‐binding sites. Our results identify the Notch signaling pathway as an important regulator of PD‐1 expression by activated CD8 + T cells.